Measurement of exposure to mouse urinary proteins in an epidemiological study. Issue 2 (February 1997) - Gordon, S; Kiernan, L A; Nieuwenhuijsen, M J; Cook, A D; Tee, R D; Newman Taylor, A J
Abstract : OBJECTIVES: To develop an assay to measure airborne mouse urinary protein (MUP) and to assess the occupational exposure to MUP in the workforce of three establishments as part of an epidemiological study examining the influence of aeroallergen exposure on the development of allergic respiratory disease. METHODS: Personal air samples were collected from nine exposure groups during a workshift. A sensitive and reproducible competitive inhibition assay, which used rabbit antisera specific for MUP, was developed and used to measure the occupational exposure to MUP. RESULTS: The personal measurements of MUP showed that people with direct contact with mice (animal technicians) had the highest exposure followed in decreasing order by those working with anaesthetised animals or their tissue (postmortem workers and scientists) and those with indirect contact with mice (supervisors, office workers, and slide production workers). The only difference in concentrations of MUP between the three establishments were found for cage cleaners, which reflected differences in working practises for this exposure category. Air samples collected during the performance of specific tasks showed that high exposures to MUP were associated with handling mice, indirect contact with mice, and washing floors. CONCLUSIONS: Exposure to mouse urinary proteins has been measured in the occupational environment. This information can be used to determine the relation between exposure to MUP and the development of allergic and respiratory disease.